Numerical modelling and parametric assessment of hybrid flat slabs with steel shear heads. (1st July 2017) - Bompa, D.V.; Elghazouli, A.Y.
Highlights: Nonlinear finite elements simulations of tests on RC and hybrid flat slabs. Parametric investigations on hybrid flat slabs with fully integrated shear heads. Modified analytical models for predicting the behaviour of hybrid flat slabs systems. Proposed expressions for determining the embedment length and section of shear head. Discussion of practical design considerations for shear heads in RC flat slabs. Abstract: This investigation examines the performance of hybrid reinforced concrete flat slabs, incorporating fully-integrated shear-heads at connections to steel columns, through a series of numerical evaluations and parametric studies. Validations of the adopted nonlinear finite element procedures, which employ concrete damage plasticity constitutive models, are carried out against experimental results on hybrid members. Complementary verifications on conventional reinforced concrete flat slabs are also undertaken to ensure the reliability of the selected ranges for key modelling parameters. Comparison of the numerical simulations against the test results shows close correlations in terms of ultimate strength, deformations and stress levels in the constituent elements of hybrid members. This is followed by a series of parametric assessments on key structural parameters for hybrid flat slabs with steel shear heads. The results of these investigations enable the identification of three modes of failure as a function of the interaction between the shear-head and surrounding concrete. The findings permit the development of improved analytical models for predicting the response as well as the ultimate strength of such members. In addition, recommendations are given for the determination of shear-head dependent parameters, which are required for practical design purposes, with a particular focus on the embedment length and section size of the shear-head elements. The suggested expressions for assessing the shear-head characteristics offer a more reliable design approach in comparison with existing methods and are suitable for effective practical application and implementation in codified procedures.